EFL UNDERGRADUATE STUDENTS’ DIFFICULTIES IN WRITING LITERATURE REVIEW OF THEIR THESIS - Yovan Dina (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
Writing a thesis is difficult for undergraduate students, especially in the writing literature review section. In the English study program at Jambi University, the students faced some difficulties in writing their literature reviews. Hence, this study aims to investigate EFL undergraduate students’ difficulties in writing the literature review of their thesis. There were two questions addressed. The first is why writing a literature review difficult for many English department students. The second is how do students overcome the difficulties in writing a literature review of their thesis. The method and design used in this research were descriptive qualitative. In-depth interviews were chosen as the instrument to collect the data. There were 8 participants of the academic years 2016 and 2017 who had been adjusted to the criteria. Based on the discussion, the students have difficulties writing a literature review such as selecting relevant references, restricted access to journals and textbooks, the language of the references was difficult to understand, lack of ability in writing a literature review, and lack of supervisor comment. However, the students have their own ways to overcome those problems.